Impacts of Implementing the Bottom-Up Economic Plan on Food Systems and Social Outcomes - International Food Policy Research Institute; Kenya Institute for Public Policy Research and Analysis; International Livestock Research Institute (International Food Policy Research Institute, 2022)
Lensa Omune, Clemens Breisinger, Xinshen Diao, Benson Kiriga, Joshua Laichena, Juneweenex Mbuthia, James Thurlow, and Joseph Karugia NPS-KIPPRA Seminar- Leveraging the new bottom-up economic plan for food System December 5, 2022.